Challenges and Realities of Teaching English at Elementary School Level In Rural Areas of Aurangabad District: Exploring the Challenges and Approaches in Teaching English at the Elementary School Level in Rural Areas of Aurangabad District (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Challenges when the English Language instructors in Indiaare tremendous and clear. They ought to have the ability to pander to thecommonsense needs of learners, to make them equipped enough to cooperate witheach other and likewise to recover informative data everywhere on the planet.English has a base in a few nations and is thought about as the most suitableand favorable apparatus for Worldwide Communication The extreme point ofEducation is to grant information to the learners, to get ready them for theirdestiny life. Instructing school scholars through chalk and talk approach hasbeen in practice for long India.Different methodologies for attaining the present objective of school trainingwere talked about and some are put into practice. The present paper attempts todecode the positive and negative focuses concerning instructing of English inschools. The outline, technique, educators and techniques for instructingEnglish is likewise presented in inborn way.